Variable resolution imaging fiber probe using digital spatial light modulator - Shinde, Anant (2018)
Flexible fiber optic imaging systems including fiber optic confocal probes have found tremendous significance in the recent past for its applications in high resolution imaging. However, motorized stage is required for scanning the sample or tip of the fiber in fiber based confocal probes. In this context, we propose a fiber probe confocal system using digital spatial light modulator devoid of using a mechanical scanning stage. Each fiberlet in the image fiber acts not only as a light conduit but also as a confocal pinhole. The paper also introduces the variation in the contrast by varying the number of illuminated fiberlets which effectively implies variation in the effective pinhole size. This approach has enabled the probe to act as an imaging unit with resolution that can be controlled and varied from a wide-field to a confocal.